N-Doped Porous Carbon-Nanofiber-Supported Fe3C/Fe2O3 Nanoparticles as Anode for High-Performance Supercapacitors - Li Li; Fengting Xie; Heyu Wu; Yuanyuan Zhu; Pinghua Zhang; Yanjiang Li; Hengzheng Li; Litao Zhao; Guang Zhu (Molecules, 2023)
Exploring anode materials with an excellent electrochemical performance is of great significance for supercapacitor applications. In this work, a N-doped-carbon-nanofiber (NCNF)-supported Fe3C/Fe2O3 nanoparticle (NCFCO) composite was synthesized via the facile carbonizing and subsequent annealing of electrospinning nanofibers containing an Fe source. In the hybrid structure, the porous carbon nanofibers used as a substrate could provide fast electron and ion transport for the Faradic reactions of Fe3C/Fe2O3 during charge–discharge cycling. The as-obtained NCFCO yields a high specific capacitance of 590.1 F g−1 at 2 A g−1, superior to that of NCNF-supported Fe3C nanoparticles (NCFC, 261.7 F g−1), and NCNFs/Fe2O3 (NCFO, 398.3 F g−1). The asymmetric supercapacitor, which was assembled using the NCFCO anode and activated carbon cathode, delivered a large energy density of 14.2 Wh kg−1 at 800 W kg−1. Additionally, it demonstrated an impressive capacitance retention of 96.7%, even after 10,000 cycles. The superior electrochemical performance can be ascribed to the synergistic contributions of NCNF and Fe3C/Fe2O3.